2015
DOI: 10.1016/j.semradonc.2014.07.002
|View full text |Cite
|
Sign up to set email alerts
|

Combination Regimens of Radiation Therapy and Therapeutic Cancer Vaccines: Mechanisms and Opportunities

Abstract: Radiation therapy is widely used with curative or palliative intent in the clinical management of multiple cancers. Although mainly aimed at direct tumor cell killing, mounting evidence suggests that radiation can alter the tumor to become an immunostimulatory milieu. Data suggest that the immunogenic effects of radiation can be exploited to promote synergistic antitumor effects in combination with immunotherapeutic agents. Here we review concepts associated with the immunogenic consequences of radiation thera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 57 publications
0
23
0
Order By: Relevance
“…For example, a promising strategy involving sequential combination of radiotherapy, vaccination and anti-PDL1 in a mouse model of pancreatic cancer converts non-T-cell-inflamed cancers into T cell-inflamed cancers and mediates regression of established pancreatic tumours 72 . Other groups are also investigating the use of irradiated tumour cell vaccines as a strategy to boost therapeutic outcomes 7375 . In one such study using a B16 melanoma model 74 , it was shown that irradiated tumour cells that were genetically modified to express murine GM-CSF stimulated potent, long-lasting and specific antitumour immunity.…”
Section: Overcoming Immunosuppressionmentioning
confidence: 99%
“…For example, a promising strategy involving sequential combination of radiotherapy, vaccination and anti-PDL1 in a mouse model of pancreatic cancer converts non-T-cell-inflamed cancers into T cell-inflamed cancers and mediates regression of established pancreatic tumours 72 . Other groups are also investigating the use of irradiated tumour cell vaccines as a strategy to boost therapeutic outcomes 7375 . In one such study using a B16 melanoma model 74 , it was shown that irradiated tumour cells that were genetically modified to express murine GM-CSF stimulated potent, long-lasting and specific antitumour immunity.…”
Section: Overcoming Immunosuppressionmentioning
confidence: 99%
“…Recent research confirms the potential usage of radiation therapy in cancer therapeutics by converting tumor to favorable condition and makes them immunostimulatory milieu [62]. Experiential data suggest that the combination of radiotherapy alongside the immunotherapeutic agents can produce the synergistic effects (Figure 3) [61,62].…”
Section: Radiation Therapy: Application In Medical Researchmentioning
confidence: 89%
“…Recent research confirms the potential usage of radiation therapy in cancer therapeutics by converting tumor to favorable condition and makes them immunostimulatory milieu [62]. Experiential data suggest that the combination of radiotherapy alongside the immunotherapeutic agents can produce the synergistic effects (Figure 3) [61,62]. From all the above-stated information, it has become clear that recent developments in radiation therapy [61,63,64] may have proven to be the most critical part in the successful development of cancer vaccine.…”
Section: Radiation Therapy: Application In Medical Researchmentioning
confidence: 91%
“…The molecular mechanisms associated with immunogenic modulation include (1) changes in tumor cell surface phenotype, (2) modulation of antiapoptotic or survival genes, or immuneresponsive genes or both, (3) modulation of antigen-processing machinery components, and (4) translocation of calreticulin to the tumor cell surface [ 90 ].…”
Section: Vaccines and Radiation Therapymentioning
confidence: 99%